Admissions to paediatric intensive care units (PICU) with refractory convulsive status epilepticus (RCSE): A two-year multi-centre study. (July 2015) - Tully, I.; Draper, E.S.; Lamming, C.R.; Mattison, D.; Thomas, C.; Martland, T.; Appleton, R.
Highlights: This audit represents the largest undertaken in children with refractory convulsive status epilepticus. The audit demonstrates many deviations from a national protocol for the treatment of convulsive status epilepticus. The short-term outcome compares favourably with previously reported data regarding mortality and morbidity. Abstract: Aims: To obtain national epidemiological data on the aetiology, management and outcome of refractory convulsive status epilepticus (RCSE) in children. Methods: Data on children admitted with RCSE between 01.01.2008 and 31.12.2009, to eight paediatric intensive care units (PICUs) were retrospectively collected using a standard proforma designed with and co-ordinated by PICANet. Results: Data were collected on 245 (male, 179) patients aged between <1 month and 16.5 years (median 2.8 years, IQR 1–7.43 years), of which: One hundred and fifty-one patients (male, 89) aged between <1 month and 16.5 years (median 2.3 years, IQR 1–7.17 years) met the study criteria for a diagnosis of RCSE. Causes included acute symptomatic (15.2%), remote symptomatic (29.0%), epilepsy-related (10.6%), progressive encephalopathy (10.6%) febrile seizures (18.2%); no cause was identified in 16.4%. First line treatments included lorazepam (118 patients, 78.1%), diazepam (72, 47.7%) and midazolam (37, 24.5%). Second-line treatments included phenytoin (125 patients, 82.8%) and phenobarbital (seven patients, 4.6%). Third-line treatments included a thiopentone bolus (99 patients, 65.6%), thiopentone infusion (20, 13.2%) midazolam infusion (56, 37.1%) phenobarbital (18, 11.9%), propofol (6, 4.0%) and clonazepam (2, 1.3%). Deviation from the national advanced paediatric life support (APLS) protocol was noted in approximately one quarter of all patients. Six patients died (4.0%). Seventeen patients (11.3%) developed a new neurological deficit on discharge from PICU, of which eight (5.3%) continued to show this deficit at a 30-day follow-up and 12 patients (7.9%) developed de novo epilepsy. Conclusions: Thiopentone was the most commonly used anticonvulsant to treat RCSE on admission to PICU. Mortality was low and approximately 1 in 25 showed a new neurological deficit at the 30-day follow-up.